In vitro and in vivo evaluations of glass-ionomer cement containing chlorhexidine for atraumatic restorative treatment - Duque, Cristiane [UNESP]; Aida, Kelly Limi [UNESP]; Pereira, Jesse Augusto [UNESP]; Teixeira, Gláucia Schuindt; Caldo-Teixeira, Angela Scarparo; Perrone, Luciana Rodrigues; Caiaffa, Karina Sampaio [UNESP]; Negrini, Thais de Cássia; de Castilho, Aline Rogéria Freire; Costa, Carlos Alberto de Souza [UNESP] (FapUNIFESP (SciELO), 2017)
Objectives: Addition of chlorhexidine has enhanced the antimicrobial effect of glass ionomer cement (GIC) indicated to Atraumatic Restorative Treatment (ART); however, the impact of this mixture on the properties of these materials and on the longevity of restorations must be investigated. The aim of this study was to evaluate the effects of incorporating chlorhexidine (CHX) in the in vitro biological and chemical-mechanical properties of GIC and in vivo clinical/ microbiological follow-up of the ART with GIC containing or not CHX. Material and Methods: For in vitro studies, groups were divided into GIC, GIC with 1.25% CHX, and GIC with 2.5% CHX. Antimicrobial activity of GIC was analyzed using agar diffusion and anti-biofilm assays. Cytotoxic effects, compressive tensile strength, microhardness and fluoride (F) release were also evaluated. A randomized controlled trial was conducted on 36 children that received ART either with GIC or GIC with CHX. Saliva and biofilm were collected for mutans streptococci (MS) counts and the survival rate of restorations was checked after 7 days, 3 months and one year after ART. ANOVA/Tukey or Kruskal-Wallis/ Mann-Whitney tests were performed for in vitro tests and in vivo microbiological analysis. The Kaplan-Meier method and Log rank tests were applied to estimate survival percentages of restorations (p<0.05). Results: Incorporation of 1.25% and 2.5% CHX improved the antimicrobial/anti-biofilm activity of GIC, without affecting F release and mechanical characteristics, but 2.5% CHX was cytotoxic. Survival rate of restorations using GIC with 1.25% CHX was similar to GIC. A significant reduction of MS levels was observed for KM+CHX group in children saliva and biofilm 7 days after treatment. Conclusions: The incorporation of 1.25% CHX increased the in vitro antimicrobial activity, without changing chemical-mechanical properties of GIC and odontoblast-like cell viability. This combination improved the in vivo short-term microbiological effect without affecting clinical performance of ART restorations.
Keywords: Chlorhexidine; Dental atraumatic restorative treatment; Glass ionomer cements